A study of common aero-allergen in Mewar region, Udaipur, Rajasthan, India - Matta, J. S.; Jain, Priyank; Ved, M. L. (International Journal of Research in Medical Sciences, 2017)
Background: Aero-allergens are important causative factor in pathogenesis of allergic respiratory diseases (Asthma, Allergic Rhinitis). Present study aimed to identify the common aeroallergens in Mewar region, Udaipur, Rajasthan, India. Methods: Intradermal allergic testing done on 1050 respiratory allergic patients in last 15 yrs (2002 to 2016) by kit containing 125 allergen extracts includes pollen, fungi, insects, dust, dander’s, fabrics, feathers and wood. In 1020 patients (after excluding 30 patients), marked positive skin reaction (3+/4+) to one or more aeroallergen noted. Results: Most common aero allergens found were pollens (62%), woods (58.5%), dander (52%), insects (45%), dust mite (44.2%) and fungi (38.4%). Among pollens most common allergens were Holoptelia integrifolia, Parthenium hysterophorn, Cynodon. Among fungi aspergillus and candida species were most common. Cockroach and fly were predominant insects. Conclusions: Role of allergen testing have important role in management of allergic respiratory diseases as allergen immunotherapy or desensitization is only disease modifying treatment.